A roadmap for CRM success : in light of the technology CSFS - Jan, Muhammad Tahir; Omar, Azura; Zain, Osman M.; Abdullah, Kalthom (JM Publishers, 2011)
The primary objective of this paper is to develop a conceptual framework that depicts the impact of technology related critical success factors (CSFs) on customer relationship management (CRM) success, namely, customer satisfaction. This paper uses a qualitative methodology that comprises of a comprehensive literature review of academic researches. Evidences from the extant literatures have suggested that four main technology CSFs; sales force automation, data warehousing & data mining, the internet, and call centres will positively affect customer satisfaction. It is also revealed that trust and privacy play the role as mediating variables between technology CSFs and CRM success. Given that this paper is a conceptual paper, there is need to embark on empirical data gathering to validate the conceptual model presented. The paper suggest that in order to satisfy the customers and make the CRM strategy work effectively, there is a need for the organisations to consider the technology CSFs because it works as an enabler of the whole CRM process. This paper primarily conceptualise a model that would assist in determining the impacts of technology CSFs on CRM success. It generally provides the organisations with CRM focus, by complementing recent works that have been conducted on the role of technology CSFs in achieving CRM success. It concluded by proposing a model for future testing.